Social and Affective Strategies Use among Arabic Language Students in Terengganu - Kamarul Shukri, Mat Teh; Nik Mohd Rahimi, Nik Yusoff; Mohamed Amin, Embi (2013)
The use of social and affective strategies in learning a second or foreign language will help students master the language learned. Therefore, this study is conducted to observe the usage level of both strategies among Arabic language students. The sample consists of 460 Form 4 students chosen at random from 13 Religous Secondary Schools in Terengganu, Malaysia. Data was collected by using a self-questionnaire to gauge the use of social and affective strategies. The results of the study showed the the usage level of social and affective strategies among the respondents is low. Hence, a pedagogical implication suggests that students should be made aware of the importance of social and affective strategies by conducting training workshops and maximizing the use of both strategies.